THE USE OF FILMS IN ACCOUNTING INSTRUCTION. - Fleig, W. J. (The Accounting Review, 1950)
The article focuses on the use of films in accounting instructions. Only few students have some knowledge of manufacturing and distribution operations. This has long been a handicap to accounting instruction. Plant visitation is one method used to acquaint students with commercial practice. A tour of a business enterprise is very desirable but may have certain disadvantages and in some instances is impractical if not impossible. Motion pictures showing commercial activities are available from many industrial concerns and associations and some schools are using these in lieu of plant visitations. A single film may feature one or more subjects including a company's general activities, the manufacture of a specific product or line of products, physical plant and equipment, employee relations, company history, research and exploration, or financial operations. Motion pictures are in many instances superior to a plant visitation. They can bring together a series of widely dispersed operations. Movies make it possible to bring to students types of industrial activities which are foreign to their locality.